Analysis of Manufacturing Process on a Corn Husker, Corn Sheller, and Corn Cob Crusher Machine Method Screw Using Motor 0.5 HP - Ulum, Miftahul; Lostari, Aini; Machfuroh, Talifatim; Supardi, Supardi; Irawan, Herry (Universitas Muhammadiyah Yogyakarta, 2025)
Corn is one of the staple foods utilized by humans as a food source and for other products; the planting, harvesting, and processing of corn significantly affect its quality. Generally, the problem faced by corn farmers is during the harvest season, where corn that is ready for harvest requires a very complicated process to obtain corn seeds. Generally, farmers perform the tasks of husking and shelling corn using their hands or makeshift tools. From this complex process, this research was conducted with the aim of designing a corn husker, corn sheller, and corn cob crusher machine. The process used in this machine is based on the principle of transfer using a screw conveyor that will move from the peeling process to the shelling process and finally to the corn cob crushing process. This research uses the method of manufacturing process analysis of several components that make up the machine and the calculation of the production cost of goods manufactured. From the results of the analysis of the research on the manufacture of the peeling machine, corn sheller, and corn cob crusher, the production cost of goods manufactured was obtained at Rp. 4,066,919, and the machine processing time was 11.4 hours